Influence of the current score on the final result in judo fights - Moussa, I. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In order to further the analysis of judo match and quantify competitive demands, it is important to estimate the influence of some match parameters [1], [2]. The purpose of the study was to develop a technical-tactical model of judo match in order to determine the probability of the outcome based on any given score throughout the match duration.